ANALISIS KEKALAHAN PASANGAN INDEPENDEN SRI MERDITOMO-KARSIDI DALAM PEMILUKADA 2011 DI KABUPATEN PATI - Icha Riani Sukma; Susilo Utomo; Nunik Retno (Journal of Politic and Government Studies, 2014)
AbstractVariety of changing in the Regent-election system since the introduction of the reformagenda is table to compel the stake-holders in a choise to make several adjustments to thechanges. The stakeholders include the candidate who participate, the success-team, and thepolitical parties that are used as the political vehicle for the candidate. This study focuses onthe political strategies of candidates and the success of the team in a competitive election.The success of a political contestation cannot be separated from the political strategyby each party. Good political strategy must be created and compiled based on the modernconcept and developments. The modern concept of political strategy has several phases thatmust be addressed, namely the situation analysis phase, the formulation phase,implementation phase, the phase of monitoring and evaluation. To that end, candidates,success-team, and political party must have skill in carrying out the various stage, in order togain political support from the community effectively and efficiently. There were six pairscandidates during the election of head regional in 2011. Among those six, one independentcandidate got the highest vote.This purpose of this study is to explain the political strategies used by Sri Merditomo-Karsidi in the election of head regional in Pati.The strategy was already planned very often still have to undergo a change in the implementation phase. The roles of alternative strategies are needed. Sometimes, the candidates and the success-team should be forced to be pragmatic for a political victory. Pragmatism is often becoming a determining factor for the success of a strategy. Consideration of last-minute swing voters and the band wagon effect, become the factor of motivation of the candidates and his success-team to be pragmatic. In fact, various commitments had to be ignored for the pragmatic considerations.Key Word: Regent Election, Political Strategy, Independent Partner.